Chicken PRDX3 is required for proliferation of chicken embryo fibroblast cells. Issue 1 (2nd January 2020) - Choi, H.; Jung, S. K.; Kim, J. S.; Oh, K. B.; Yang, H.; Lee, G.; Lee, H.-C.; Woo, J.-S.; Byun, S. J.
ABSTRACT: 1. This experiment investigated the influence of chicken PRDX3 on cell proliferation in chick embryo fibroblast cells using PRDX3 knockdown technology. 2. A methyl thiazolyl tetrazolium (MTT) assay was performed to assess the effect of chPRDX3 knockdown on fibroblast proliferation. The antioxidant effect was investigated to determine if it directly mediated fibroblast cell proliferation. 3. To determine the role of chPRDX3 on cell proliferation, an siRNA mediated knockdown was performed in chick fibroblast cells using an in vitro assay. The proliferation of fibroblast cells transfected with s iPRDX3 #3 and siPRDX3 Mix was significantly decreased after 48 h (P < 0.01). In addition, the knockdown of chicken PRDX3 suppressed cell proliferation through an increase in oxidative stress. 4. The results demonstrated that chPRDX3 is required for cell proliferation in chicken fibroblast cells. Such findings have important implications for the maintenance of chicken fibroblast cells.